Defenseman goal scoring analysis from the 2013-2014 National Hockey League season - Marshall, M. (2015)
The purpose of this thesis is to determine how defenseman score goals. Scoring goals is an important part of the game but often over looked by a defenseman. The main object is to see how the goals are scored and if there are certain ways that most goals are scored. Previous research has been done on goal scoring as a whole, but very few, if not any have been done on defenseman goal scoring, The work and findings were done using the 2013/2014 NHL season. Using different variables, the goals were recorderd to show what was involved in how the goal was scored. The results for defenseman scoring that can be made are that quick, accurate shots are the best shooting type to score. Getting to the middle of the ice and shooting right away was also a key finding. For defenseman, it was important that when the puck is received, either shot right away or to hold onto the puck and wait till a play develops in front of the net.